A-KETOGLUTARATE- AND SODIUM MALATE-INCORPORATED BIOACTIVE FILMS BASED ON POLY(VINYL ALCOHOL): PREPARATION AND CHARACTERIZATION. (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article presents the preparation of bioactive films based on poly(vinyl alcohol) (PVA/PVS) incorporating A-ketoglutarate (α-ketoglutarate) and sodium malate, and evaluates their physicochemical and functional properties. PVA is a water-soluble, biocompatible, film-forming polymer that can develop network-like structures through hydrogen bonding and, under suitable conditions, esterification/crosslinking when combined with organic acids and their salts.